Implementation of consumer rights, obligations, and business actors' responsibilities in case of non-conforming goods - Azhar Rahadiyan Anwar; Inosentius Samsul (IHSA Institute, 2023)
Today, consumer protection should receive more attention because there are not a few Business Actors who do business in Indonesia, both domestic and foreign Business Actors and are part of Indonesia's economic development. This paper will investigate the responsibility of the Seller in the event of a discrepancy in the delivery of goods to customers, as well as the legal remedies available to consumers. The research method used was normative method or doctrinal legal research. Because consumers' rights and obligations in transactions with business actors are often regulated and have the type of a standard that business actors must give consumers. Business actors are responsible for failing to provide consumer rights. In the Consumer Protection Law,